Educational Background and Gender Factors Affecting Sales Turnover of SMEs Sugar Ants Entrepreneur - Titis Nistia Sari; Dabella Yunia; Edy Arisondha (Universitas Gorontalo, 2021)
The purpose of this study was to determine the influence of educational background and gender on the sales turnover of UKM Sugar Ant Entrepreneurs. The method used is SEM PLS 3 with a population of 50 respondents of SMEs Sugar Ant Entrepreneurs. The results of the study found that educational background had a positive effect on sales turnover of SMEs Sugar Ant Entrepreneurs, while gender did not have a positive effect on sales turnover of SMEs Sugar Ants Entrepreneurs. So, the Sugar Ant Entrepreneurs who are in Lebak Banten in obtaining sales turnover are not determined by gender itself, but are determined by educational background